Designing augmentative and alternative communication applications: the results of focus groups with speech-language pathologists and parents of children with autism spectrum disorder. (19th May 2018) - Boster, Jamie B.; McCarthy, John W.
Abstract: Purpose: The purpose of this study was to gain insight from speech-language pathologists (SLPs) and parents of children with autism spectrum disorder (ASD) regarding appealing features of augmentative and alternative communication (AAC) applications. Method: Two separate 1-hour focus groups were conducted with 8 SLPs and 5 parents of children with ASD to identify appealing design features of AAC Apps, their benefits and potential concerns. Participants were shown novel interface designs for communication mode, play mode and incentive systems. Participants responded to poll questions and provided benefits and drawbacks of the features as part of structured discussion. Results: SLPs and parents identified a range of appealing features in communication mode (customization, animation and colour-coding) as well as in play mode (games and videos). SLPs preferred interfaces that supported motor planning and instruction while parents preferred those features such as character assistants that would appeal to their child. Overall SLPs and parents agreed on features for future AAC Apps. Conclusion: SLPs and parents have valuable input in regards to future AAC app design informed by their experiences with children with ASD. Both groups are key stakeholders in the design process and should be included in future design and research endeavors. Implications for Rehabilitation: AAC applications for the iPad are often designed based on previous devices without consideration of new features. Ensuring the design of new interfaces are appealing and beneficial for children with ASD can potentially further support their communication. This study demonstrates how key stakeholders in AAC including speech language pathologists and parents can provide information to support the development of future AAC interface designs. Key stakeholders may be an untapped resource in the development of future AAC interfaces for children with ASD.